The Tomb of Two Priestesses? The Late Neo-Elamite Jubaji Tomb in a Religious-Royal Context - Yasmina Wicks; Gian Pietro Basello (Asia Anteriore Antica)
This article revisits one of the most significant archaeological discoveries in southwest Iran in recent decades, a rich early-mid 6th century BCE tomb of two women, unearthed near the village of Jubaji on the Ramhormoz plain in 2007. Based on the sumptuous grave assemblages and the inclusion of a gold ceremonial ‘ring’ inscribed with the name of a late Neo-Elamite king, Šutur-Nahunte son of Intata, the tomb’s excavator, Arman Shishegar, reasonably interpreted the women – one aged under 17 years, the other 30-35 years – as princesses. Here it is argued that the women may have been important figures in a religious institution based on a combination of the context of the tomb, which seems to have been in an association with a monumental structure, and certain elements of the assemblages. While none of the individual items is significant in isolation, when put together they are highly suggestive of a cultic environment. These include several semiprecious stone beads, including two inscribed eye-stones, that were already very ancient when deposited, special ritual paraphernalia, the bronze coffins that held the women’s remains, the inscribed gold ‘ring’ naming Šutur-Nahunte son of Intata, and an inscribed gold object (perhaps a bracelet) of a cult officiant. This is not to say that the roles of princess and priestess were by any means mutually exclusive, but it is the religious aspect that has yet to be investigated. A reassessment here of the significance of the inscribed objects from the Jubaji tomb in a religious context is taken as an occasion to publish new transliterations, translations, and analyses of the inscriptions by Gian Pietro Basello.